5D.02: WHY DOES WAKAYAMA PREFECTURE HAVE THE HIGHEST RATES OF HYPERTENSION IN JAPAN? CONSIDERATION ON EXERCISE INCORPORATED INTO EVERYDAY LIFE. (June 2015) - Oka, M.; Kaneda, M.; Sasabe, S.; Yamamoto, M.; Ito, K.; Miyai, N.; Utsumi, M.; Shiba, M.; Arita, M.
Abstract : Objective: In Japan, there are 47 prefectures with differences in topography, industrial structure, population distribution and hypertension rate as well. The authors' home prefecture of Wakayama has the highest incidence of hypertension in the nation at 25.0%. This shows 7.6 point spread compared with the prefecture with the lowest rate at 17.4%. The aim of our study is to search for the reasons of high rate of hypertension in Wakayama, and to consider effective prevention of hypertension in Wakayama as well as in Japan. Design and method: Correlation analysis was performed using hypertension rate for each prefecture versus the variables of: 1. salt intake, 2. vegetable intake, 3. alcohol habits, 4. smoking habits, and 5. walking paces per day (walking), using 5% significance level. To find the social causes that impact walking, correlation analysis was performed with the variables of: 1. number of train stations, 2. vehicle ownership rate, 3. light-vehicle ownership rate, and 4. slope of habitable areas (index of steepness), versus walking, as well as hypertension rate. Lastly, with hypertension rate as the dependent variable, all aforementioned variables, adding the rate of health examination and the number of hospitals, multiple regression analysis was performed. Results: There was a significant negative correlation between hypertension rate and walking (r = -0.440, p = 0.004). Walking was positively correlated with number of train stations (0.381, 0.008) and negatively with vehicle ownership rate (-0.424, 0.003) as well as light-vehicle ownership rate (-0.616, 0.000). Hypertension rate was most strongly affected by walking and slope. There were no significant correlations for the salt, vegetable, alcohol, smoking, rate of health examination, or number of hospitals. R2 coefficient was 0.442. Conclusions: It is suggested that high incidence of hypertension in Wakayama may be due to less walking habits. In the prefectures with larger mountainous areas where transportation rely on vehicle rather than train, people walked less. Use of light-vehicle particularly reduced walking. It is suggested that the daily habits shaped by the characteristics of living environments such as topography and transportation infrastructure could affect the habitants' health.